Digital Campaign Instagram Account @Teensgogreen.id in Promoting Environmental Activism in the Younger Generation - Putri Lestari, Andini; Deslia, Iva Fikrani (Jogjakarta Communication Conference (JCC), 2024)
Teens Go Green is a community that actively carries out environmental activities with a volunteer concept. Teens Go Green carries out a campaign on Instagram as a tool. The campaign carried out by Teens Go Green creates content in the form of interesting invitations so that the millennial generation can be interested. This is because the digital campaign that Teens Go Green has on Instagram has been conveyed so that it has an impact on changes in behavior. Using a qualitative approach research method through interviews, observation. Communication activities on the Instagram account @teensgogreen.id are studied through Digital Campaign Theory and Cyberactivism Theory. The results of this research show that Teens Go Green has an environmental care program and interviewed one of the informants who is an Instagram follower who also participated in one of the activities organized by Teens Go Green and also interviewed the Founder of Teens Go Green Indonesia. Based on posts uploaded to the Instagram account @ teensgogreen.id, they were able to respond to changes in the behavior of Instagram followers who contributed to the activities held by Teens Go Green and increased awareness of the millennial generation to preserve the environment.